Dysfunction of inhibitory interneurons contributes to synaptic plasticity via GABABR-pNR2B signaling in a chronic migraine rat model - Zeng, Xiaoxu; Niu, Yingying; Qin, Guangcheng; Zhang, Dunke; Chen, Lixue (Frontiers in Molecular Neuroscience, 2023)
Background: According to our previous study, the loss in the function of inhibitory interneurons contributes to central sensitization of chronic migraine (CM). Synaptic plasticity is a vital basis for the occurrence of central sensitization. However, whether the decline of interneurons-mediated inhibition promotes central sensitization by regulating synaptic plasticity in CM remains unclear. Therefore, this study aims to explore the role of interneurons-mediated inhibition in the development of synaptic plasticity of CM. Methods: A CM model was established by infusing inflammatory soup (IS) into the dura of male Wistar rats for seven days, function of inhibitory interneurons was evaluated. After intraventricular injection of Baclofen (a gamma-aminobutyric acid type B receptor (GABABR) agonist) or H89 (a protein kinase A (PKA) inhibitor), behavioral tests were performed. The changes in synaptic plasticity were investigated by determining the levels of synaptic-associated proteins postsynaptic density protein 95 (PSD95), synaptophysin (Syp) and synaptophysin-1(Syt-1), synaptic ultrastructure under transmission electron microscopy (TEM) and the density of synaptic spines via Golgi-Cox staining. Central sensitization was evaluated through measuring calcitonin related gene peptide (CGRP), brain-related neurotrophic factor (BDNF), c-Fos and substance P (SP) levels. Finally, the PKA/Fyn/tyrosine phosphorylation of NR2B (pNR2B) pathway and pNR2B downstream calcium-calmodulin-dependent kinaseⅡ(CaMKⅡ)/c-AMP-responsive element binding protein (pCREB) signal were assessed. Results: We observed dysfunction of inhibitory interneurons, the activation of GABABR2 ameliorated CM-induced hyperalgesia, repressed CM-evoked elevation of synaptic-associated proteins and enhancement of synaptic transmission, alleviated CM-triggered increases of central sensitization-related proteins, and inhibited the CaMKⅡ/pCREB siganl by the PKA/Fyn/pNR2B pathway. The inhibition of PKA suppressed the CM-induced activation of the Fyn/pNR2B signal. Conclusions: These data reveal that the dysfunction of inhibitory interneurons contributes to central sensitization by regulating synaptic plasticity through the GABABR2/PKA/Fyn/pNR2B pathway in the periaqueductal gray (PAG) of CM rats. The blockage of the GABABR2-pNR2B signal might have a positive influence on the therapy of CM through modulating synaptic plasticity in central sensitization.